Pemodelan E-Learning Dengan Framework Learning Technology System Architecture (LTSA) Pada Stmik Pranata Indonesia - Spits Warnars, Harco Leslie Hendric (Jurnal Sistem Komputer, 2015)
The development of information and communication technology influences the changing from conventional into digital education which is recognized as e-learning. Most of education institution has employee students which have to spare their time between doing their higher education and working, including STMIK Pranata Indonesia. This is important for STMIK Pranata Indonesia to builds e-learning in order to support most of their students which are recognized as employee students. E-learning is modelled with Learning Technology System Architecture (LTSA) framework which is recognized as IEEE standard to build e-learning. At the end, this e-learning will help lecturers and students in academy teaching process.